Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—19. Odontocheila microptera nom. nov., a new replacement name for O. euryoides W. Horn, 1922, and lectotype designation of O. nitidicollis (Dejean, 1825) (Coleoptera: Cicindelidae) - Moravec, Jiří; Huber, Ronald; Brzoska, David (Zootaxa, 2017)
A new replacement name Odontocheila microptera nom. nov. for Odontocheila euryoides W. Horn, 1922 that is a junior primary homonym of Odontocheila bennigseni euryoides W. Horn, 1906 (currently Euryarthron bennigseni euryoides), is introduced. It has been confirmed that O. microptera, due to its atrophic thoracic wings, is the only flightless species of the genus and of the whole subtribe Odontocheilina W. Horn, 1899 sensu Moravec (2012). Redescription and illustrations of the habitus, diagnostic characters and biotope of this hitherto little know species, as well as of the similar O. nitidicollis (Dejean, 1825), along with the lectotype designation of the latter, are presented. Distributions and habitat of both species are treated and discussed.